SANKSI HUKUM TERHADAP PELAKU KORUPSI (Perspektif Undang-undang Pemberantasan Korupsi dan Hukum Islam) - Rahmayanti, Rahmayanti (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2017)
Corruption in Law No. 20 of 2001, corruption is systematic and widespread, not only financial harm and the country's economy, but also a violation of the rights of the social and large economic society, so it is classified as an extraordinary crime, its eradication must be done in a way that is remarkable that in accordance with the laws corruption eradication. However, in the Islamic concept law is very difficult to categorize the offense of corruption as sirqah (theft ). This is due to the diversity of corruption itself is generally not included in the definition of sariqah ( theft ). Then the fuqaha explain corruption sanctioned by the benefit being ta'zir implementation judges handed in their ijtihad . Keywords: Sanctions, Law, Criminal, Corruption, Law, Islamic Law